Problematika Keadilan Hukum yang lemah : ditinjau dari NKRI sebagai Negara Kesatuan - Muhammad Ammar Imaddudin (Jurnal Ilmu Politik dan Pemerintahan, 2020)
Weak Problematics Law: viewed from NKRI as a Unity State Weak law in Indonesia cannot uphold the truth, even the development programs and budgets that have been provided, corruption always undermines existing funds. In law enforcement starting from the Police, Corruption Eradication Commission (KPK), Legal Counsel and up to the civil prison officers must take part in it. The problem grew even though the law had been passed and applied, but until a certain time limit the regulation of its implementation had not yet been made as an order of the Act, so that as a result several articles of the Act could not be implemented. The process of accepting law enforcement has actually met the conditions of producing, for example, police officers who have good ability to serve the community. But in reality, the admissions process is often tainted by bribes or a small number of people who want to become members of law enforcement. Therefore, the quality of the members of law enforcement needs to be questioned and many are not in accordance with what has been determined. As a result, law enforcement tends to be less than the number of people who continue to grow, so that law enforcement officials can not carry out their duties to the maximum as a means of law enforcement. In other contexts but still within the legal shutter, development has been going well, Indonesia already has large capital in development, large natural resources, and others. Even Indonesia's economic growth is ranked 16th in the world. By knowing and understanding these matters, it should be easy for law enforcers to identify the values and norms or rules that apply in the environment. In broad outline, the community in Indonesia is divided into two groups namely the upper classes (rich people) and the lower classes (poor people). Law enforcement between the two is very different. This is because themindset and knowledge are clearly different.